Simulation of Angle-insensitive Microwave Metamaterial Absorbers Operating at Transmission Mode - Tran, Van Huynh; Vu, Dinh Lam; Nguyen, Thanh Tung (Communications in Physics, 2021)
Metamaterial absorbers with the resonator/dielectric/metallic-mirror conventional design are often angle-dependent and completely reflective outside the absorption band. Herein we have proposed a novel solution to achieve an angle-insensitive bidirectional absorber operating at transmission mode using a simple metamaterials system. The proposed system is composed of two symmetric disk-pair layers, called the disk-pair dimer, that exhibited two identical but coupled magnetic resonances at the same frequency. This unique design allows to absorb the electromagnetic energy at the transmission mode, which is rarely achieved in the conventional modes. By optimizing the coupling strength between two disk-pair layers, a total absorptivity could be enhanced up to 90%